2020
DOI: 10.1186/s40463-020-00421-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph node ratio in laryngeal and hypopharyngeal squamous cell carcinoma: A systematic review and meta-analysis

Abstract: Background: Several recent studies have indicated that the lymph node ratio (LNR) is an independent prognostic factor for laryngeal and hypopharyngeal squamous cell carcinoma (LHSCC). The purpose of this paper is to assess the prognostic value of LNR and explore appropriate cutoff values by conducting a systematic review and metaanalysis. Methods: Pubmed, Embase (via Ovid), and Cochrane library were systematically searched for studies on the prognostic value of LNR in LHSCC up to October 31, 2019. Then, Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 40 publications
1
41
1
Order By: Relevance
“…The cumulation of tobacco could hardly be eliminated even after primary TL. It was recognized by several studies that the tumor invasive ability manifests largely in the form of lymph node ratio 11 , 23 , 24 . Patients with a higher LNR had inferior long-term survival than those with low LNR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulation of tobacco could hardly be eliminated even after primary TL. It was recognized by several studies that the tumor invasive ability manifests largely in the form of lymph node ratio 11 , 23 , 24 . Patients with a higher LNR had inferior long-term survival than those with low LNR.…”
Section: Discussionmentioning
confidence: 99%
“…Age was classified into two groups (<60 and ≥60). The cut-off point for lymph node ratio (LNR) was previously reported ranging from 0.03 to 0.14 10 , 11 , and in this study, we used using the “X-tile” program (Yale University, USA) to obtain the optimal point 12 . Accordingly, the LNR was divided into three groups (< 0.03, ≥ 0.03, no neck dissection).…”
Section: Methodsmentioning
confidence: 99%
“…It would not be surprising that the addition of clinicopathological features such as tumor invasion status or lymph node disseminated the extent and radiographic information from regional lymphadenopathies will improve the current RS model. Previous studies demonstrated that male sex, advanced age, tumor size, tumor invasion, lymph node stage, comorbid conditions, poor performance scores, human papillomavirus infection, and programmed death ligand-1 expression level are poor prognostic factors in patients with HPSCC [45][46][47]. Although radiomic research studies are still emerging, our RS model provided higher sensitivity and specificity than tumor volume in predicting locoregional recurrence in patients with advanced HPSCC, indicating that, in addition to clinicopathological factors, RS is a useful tool for predicting local failure in patients with advanced HPSCC who want to receive OPT.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Two more pathological indices related to neck dissection that have also proven their independent prognostic value in head and neck squamous cell carcinoma are lymph node yield and lymph node ratio. [9][10][11][12][13][14][15][16][17][18] While the lymph node yield is the total number of lymph nodes removed in a given neck dissection, the lymph node ratio (also known as lymph node density) represents the ratio of metastatic lymph nodes to the total number of lymph nodes harvested. Though lymph node yield and lymph node ratio are yet to find their places in mainstream clinical guidelines and practice, they are the only available parameters at present for qualifying and quantifying the adequacy of neck dissection.…”
Section: Introductionmentioning
confidence: 99%
“…From a prognostic point of view, numerous systematic reviews and meta-analyses have highlighted that the survival rates in head and neck squamous cell carcinoma can be improved by increasing the lymph node yield or by decreasing the lymph node ratio. [13][14][15][16][17] As a result, surgeons and pathologists worldwide have been looking for effective ways to increase the lymph node yield and reduce the lymph node ratio. [19][20][21][22][23] Apart from the expertise and dedication of the surgeon and the pathologist, a few other determinants could also affect these outcomes of neck dissection.…”
Section: Introductionmentioning
confidence: 99%